Extreme thrombocytosis is associated with critical illness and young age, but not increased thrombotic risk, in hospitalized pediatric patients. (21st October 2020) - Thom, Christopher S.; Echevarria, Emily; Osborne, Ashley D.; Carr, Leah; Rubey, Kathryn M.; Salazar, Elizabeth; Callaway, Danielle; Pawlowski, Thomas; Devine, Matthew; Kleinman, Stacey; Witmer, Char; Flibotte, John; et al.
Abstract: Background: Extreme thrombocytosis (EXT, platelet count > 1000 × 10 3 /μL) is an uncommon but potentially clinically significant finding. Primary EXT in the setting of myeloproliferative disorders is linked to thrombotic and/or bleeding complications more frequently than secondary EXT, which typically occurs in reaction to infection, inflammation, or iron deficiency. However, comorbidities have been reported in adults with secondary EXT. Clinical implications of EXT in children are not well defined, as prior studies targeted small and/or specialized pediatric populations. Objectives: Our objectives were to determine etiologies and sequelae of EXT in a hospitalized general pediatric patient population. Patients and Methods: We retrospectively analyzed EXT cases from a single‐center pediatric cohort of ~80 000 patients over 8 years. Results: Virtually all cases (99.8%) were secondary in nature, and most were multifactorial. Many cases of EXT occurred in children under 2 years old (47%) and/or during critical illness (55%). No thrombotic or bleeding events directly resulted from EXT, confirming a paucity of clinical complications associated with EXT in pediatric patients. There were indications that neonatal hematopoiesis and individual genetic variation influenced some cases, in addition to certain diagnoses (eg, sickle cell anemia) and clinical contexts (eg, asplenia). Conclusion: Our findings confirm that thrombotic events related to EXT are rare in pediatric patients, which can inform the use of empiric anti‐platelet therapy.